PERENCANAAN STRUKTUR APARTEMEN 40 LANTAI TAHAN GEMPA DI DEPOK DAN PEMERIKSAAN KINERJA DENGAN ANALISIS PUSHOVER - Muharzaki Putri, Wirza
Number of high rise building construction in Indonesia has always increased along with the growth of the population in Indonesia. High rise buildings in Indonesia are planned as earthquake-resistant structures since Indonesia is located in high earthquake potential area. There are two stages of analysis used, namely dynamic analysis of spectrum response and nonlinear static analysis (pushover). Dynamic analysis of spectrum response refers to SNI 1726-2012, which aims to obtain structural behavior after being given an earthquake load. Nonliner static analysis (pushover) refers to FEMA 451B, which aims to determine the maximum force and deformation that can occur, so that the performance level of the structure can be determined. In this final project, a model of high rise apartment buildings in Depok with an asymmetrical structure of 40 floors is planned to be resistant to earthquakes. The methodology planned in this final project such as initial structure planning, structural modelling in software ETABS, dynamic analysis of structural spectrum responses, design of structural elements, and nonlinear static analysis (pushover).